Improving the imaging performance of the 1.5 T MR-linac using a flexible, 32-channel, on-body receive array. (2nd November 2020) - Zijlema, Stefan E; Tijssen, Rob H N; van Dijk, Luca; Hackett, Sara L; Wolthaus, Jochem W H; Breimer, Wico; Lagendijk, Jan J W; van den Berg, Cornelis A T
Abstract: High impedance coils (HICs) are suitable as a building block of receive arrays for MRI-guided radiotherapy (MRIgRT) as HICs do not require radiation-attenuating capacitors and dense support materials. Recently, we proved the feasibility of using HICs to create a radiation transparent (i.e. radiolucent) window. In this work, we constructed a fully functional 32-channel array based on this design. The anterior element is flexible and follows the shape of the subject, while the posterior element is rigid to support the subject. Both elements feature a 2 × 8 channel layout. Here, we discuss the construction process and characterize the array's radiolucency and imaging performance. The dosimetric impact of the array was quantified by assessing the surface dose increase and attenuation of a single beam. The imaging performance of the prototype was compared to the clinical array in terms of visual appearance, signal-to-noise ratio (SNR), and acceleration performance, both in phantom and in-vivo measurements. Dosimetry measurements showed that on-body placement changed the anterior and posterior surface dose by +3% and −16% of the dose maximum. Attenuation under the anterior support materials and conductors was 0.3% and ≤1.5%, respectively. Phantom and in-vivo imaging with this array demonstrated an improvement of the SNR at the surface and the image quality in general. Simultaneous irradiation did not affect the SNR. G-factors were reduced considerably and clinically used sequences could be accelerated by up to 45%, which would greatly reduce pre-beam imaging times. Finally, the maximally achievable temporal resolution of abdominal 3D cine imaging was improved to 1.1 s, which was > 5 × faster than could be achieved with the clinical array. This constitutes a big step towards the ability to resolve respiratory motion in 3D. In conclusion, the proposed 32-channel array is compatible with MRIgRT and can significantly reduce scan times and/or improve the image quality of all on-line scans.